Miocene quartz sands redeposited on subaqueous and alluvial fans during the Saalian: Interpretation of the depositional scenario at Ujście, western Poland - Mleczak, Mateusz; Pisarska-Jamroży, Małgorzata (Geologos, 2019)
The 14-m-thick sandy succession at Ujście in western Poland formed during the Odranian stadial of the Saalian glaciation, is exceptional in being very well sorted, almost mono-fractional (fine-grained sands) and mono-mineral (mainly quartz grains) and in lacking Scandinavian erratics. The lower sequence (5 metres in thickness) consists of three stacked packages of clinoforms (inclined cross-stratified sands) and is interpreted as having been deposited on a subaqueous fan in a shallow lake during two phases of rising water levels. The upper sand (9 metres in thickness) with (sub) horizontal stratification was redeposited on a subaerial alluvial fan. Distinctive distributary channels that occur in the uppermost part of the subaqueous fan and in the lowermost portion of the alluvial fan may indicate a change in sedimentation style from subaqueous to subaerial. Moreover, the subaerial position of the fan supports the presence of ice-wedge casts that developed under periglacial conditions in the upper part of alluvial fan. The results of granulo-metric analysis, rounding and frosting of grains and mineral analysis indicate that the sands are derived from Gorzów Formation of Early Miocene age. The only feasible explanation is that the 14-m-thick unit must have been redeposited during the Saalian glaciation.